Does Vocational Still Imply Tracking? Examining the Evolution of Career and Technical Education Curricular Policy in Texas. Issue 7 (November 2019) - Giani, Matt S.
Vocational education has historically been viewed as a mechanism for reinforcing social stratification by channeling underrepresented students into pathways with limited educational and economic benefits. However, vocational education has evolved significantly over time, most notably with the shift to career and technical education (CTE) in the Carl D. Perkins Act of 2006 (Perkins IV). Texas began reforming its approach to CTE around 2009 in response to Perkins IV. This study compared demographic patterns in CTE participation and the relationship between CTE concentration and postsecondary access for two cohorts of Texas high school graduates, the latter of which began high school under the new CTE policy. The results reveal limited stratification in CTE participation and a positive relationship between CTE concentration and postsecondary access overall, and in particular enrollment in public 4-year colleges, for the latter cohort. The results suggest CTE may be becoming more effective at providing pathways to postsecondary.